Decision-making in agribusiness based on Artificial Intelligence - Bandeira, Marina Valim; Móta, Léia Michele Ferreira de Souza; Behr, Ariel (Revista de Administração da UFSM, 2022)
Purpose: Artificial Intelligence (AI) tools have become popular in the most diverse contexts of use. This research sought to investigate how AI tools were applied in agribusiness by assisting producers in decision-making. Design / methodology / approach: To this end, online and semi-structured interviews were conducted with managers and rural producers who use this type of technology on their properties. Findings: AI was found to be present in machinery, software, and other applications applied for crop monitoring, soil quality verification, and management in general. Users are quite optimistic with the results, especially in decision support during planting period. These differences are perceived before and after technologies utilization. However, interviewers still believe that the human presence is fundamental in the farming. Research limitations / implications: As limitations, it is highlighted the schedule for conducting the interviews, as well as the fact that they were performed online. Despite this, it was possible to verify the importance of the use of technology for the agribusiness sector, serving as support for the management of rural properties. Originality / value: In the Information Systems studies field to relate the use of AI and decision-making in a sector such as agribusiness is something recent and innovative.